ANALISIS PERILAKU STICKY COST BIAYA PENJUALAN DAN BIAYA ADMINISTRASI & UMUM PADA PERUSAHAAN NON-CYCLICALS TAHUN 2022-2024 - Gracia Helena Pasapan; I Melda Dyah Fitriani; L.M Hasriadi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
Cost behavior is not always symmetric in response to changes in business activity. Sticky cost phenomenon occurs when costs increase more when sales rise than they decrease when sales fall, potentially reducing a company’s efficiency and profitability. This study aimed to analyze sticky cost behavior in selling costs and general and administrative costs among Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange for the period 2022–2024. A quantitative method with an associative approach was employed. Purposive sampling yielded 86 sample companies with 248 observations. Hypotheses were tested using multiple linear regression with an interaction variable as the primary sticky cost indicator. The results indicate that neither selling costs nor general and administrative costs exhibit significant sticky cost behavior. Both hypotheses are rejected, suggesting that companies in this sector tend to be flexible in adjusting operating costs in response to changes in sales revenue.